THE INFLUENCE OF THE CENTRAL BANK IN THE SPREAD OF «CONTAGION EFFECT» ON THE INTERBANK MARKET - V. E. Gladkova (Модернизация, инновация, развитие)
The paper studies the degree of development and the theoretical foundations of international experience in the exploration of two independent directions: the first one related to the concept, the question of the role and necessity of lender of last resort, while the latter, in turn, is connected with the problem of the spread of bankruptcies in the banking system, known in literature as the «contagion effect».